The Role of Social Norms in the Portion Size Effect: Reducing Normative Relevance Reduces the Effect of Portion Size on Consumption Decisions - Versluis, Iris; Papies, Esther K. (Frontiers in Psychology, 2016)
People typically eat more from large portions of food than from small portions. An explanation that has often been given for this so-called portion size effect is that the portion size acts as a social norm and as such communicates how much is appropriate to eat. In this paper, we tested this explanation by examining whether manipulating the relevance of the portion size as a social norm changes the portion size effect, as assessed by prospective consumption decisions. We conducted one pilot experiment and one full experiment in which participants respectively indicated how much they would eat or serve themselves from a given amount of different foods. In the pilot (N = 63), we manipulated normative relevance by allegedly basing the portion size on the behavior of either students of the own university (in-group) or of another university (out-group). In the main experiment (N = 321), we told participants that either a minority or majority of people similar to them approved of the portion size. Results show that in both experiments, participants expected to serve themselves and to eat more from larger than from smaller portions. As expected, however, the portion size effect was less pronounced when the reference portions were allegedly based on the behavior of an out-group (pilot) or approved only by a minority (main experiment). These findings suggest that the portion size indeed provides normative information, because participants were less influenced by it if it communicated the behaviors or values of a less relevant social group. In addition, in the main experiment, the relation between portion size and the expected amount served was partially mediated by the amount that was considered appropriate, suggesting that concerns about eating an appropriate amount indeed play a role in the portion size effect. However, since the portion size effect was weakened but not eliminated by the normative relevance manipulations and since mediation was only partial, other mechanisms may also play a role.